2011
DOI: 10.1111/j.1365-2648.2011.05701.x
|View full text |Cite
|
Sign up to set email alerts
|

A path model of health-related quality of life in Type 2 diabetic patients: a cross-sectional study in Taiwan

Abstract: Nurses should develop new approaches to improve various aspects of health-related quality of life. Nurses could empower patients to improve satisfaction aspect of health-related quality of life. To improve the impact and worry aspects of health-related quality of life, nurses should reduce diabetes distress felt by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 31 publications
5
36
1
2
Order By: Relevance
“…Adherence to the multidimensional, self-care regimen is challenging (Zulman, Rosland, Choi, Langa, & Heisler, 2012) and places a significant burden on physical and mental well-being (Wang, Wu, & Hsu, 2011). Various external factors like availability of social support, psychological factors such as self-efficacy (Hunt, Grant, & Pritchard, 2012;Strom & Egede, 2012), socioeconomic factors (e.g., low income, employment status; Debussche, Balcou- Debussche, Besancon, & Traore, 2009), demographic factors (e.g., gender, religion, marital status, educational status, expectation regarding aging [ERA]; Kart, Kinney, Subedi, Basnyat, & Vadakkan, 2007;Karter et al, 2007;Kiberenge, Ndegwa, Njenga, & Muchemi, 2010;Shrestha, Kosalram, & Gopichandran, 2013), cultural factors (Nam, Chesla, Stotts, Kroon, & Janson, 2011;Shrestha et al, 2013), and disease-related factors (like presence of DM-related complications, presence of comorbidities; Song et al, 2012) have been identified to affect self-care behaviors of adults with DM.…”
Section: Self-care Behaviorsmentioning
confidence: 99%
“…Adherence to the multidimensional, self-care regimen is challenging (Zulman, Rosland, Choi, Langa, & Heisler, 2012) and places a significant burden on physical and mental well-being (Wang, Wu, & Hsu, 2011). Various external factors like availability of social support, psychological factors such as self-efficacy (Hunt, Grant, & Pritchard, 2012;Strom & Egede, 2012), socioeconomic factors (e.g., low income, employment status; Debussche, Balcou- Debussche, Besancon, & Traore, 2009), demographic factors (e.g., gender, religion, marital status, educational status, expectation regarding aging [ERA]; Kart, Kinney, Subedi, Basnyat, & Vadakkan, 2007;Karter et al, 2007;Kiberenge, Ndegwa, Njenga, & Muchemi, 2010;Shrestha, Kosalram, & Gopichandran, 2013), cultural factors (Nam, Chesla, Stotts, Kroon, & Janson, 2011;Shrestha et al, 2013), and disease-related factors (like presence of DM-related complications, presence of comorbidities; Song et al, 2012) have been identified to affect self-care behaviors of adults with DM.…”
Section: Self-care Behaviorsmentioning
confidence: 99%
“…Emotional distress is an important problem for patients with diabetes, and previous studies have correlated emotional distress negatively with diabetes self-care behaviors and glycemic control (Ogbera & AdeyemiDoro, 2011;Wang, Wu, & Hsu, 2011). Emotional distress not only impacts the mental health of patients with diabetes but also affects their diabetes control.…”
Section: Introductionmentioning
confidence: 97%
“…In one longitudinal study, people with type-2 diabetes were more likely to have high levels of diabetes distress if they were women, had diabetes complications, had experienced negative life events, had previously been depressed and had eaten unhealthily or been less physically active [15]. Previous cross-sectional research, primarily among people with type-2 diabetes, has found high diabetes distress to be associated with low quality of life and difficulties in managing diabetes in everyday life such as low self-efficacy, low diabetes empowerment, unhealthy diet and less physical activity [4,9,[11][12][13][14]. Furthermore studies have suggested that high diabetes distress is associated with high levels of HbA1c [9,10,12].…”
Section: Introductionmentioning
confidence: 98%